Desenvolvimento e Integração de um Sistema de Servidor web Baseado com Arquitetura em Nuvem para Robótica Educacional - Kusumota, Victor Luis Pires (Universidade Federal de São Carlos, 2019)
Robotics is an attractive and motivating tool for students of any level. Using robots in education can help to arouse students’ interest in many subjects. This work presents the development and implementation of an educational platform for a mobile robot called Cozmo, with several features, including web server for user interface, computer vision, voice recognition, robot trajectory tracking control, among others. Functions for Educational purposes were implemented in the developed system, including mathematical, spelling, directions, and questions functions that gives more flexibility for the teachers to create their own scripts. A cloud voice recognition tool was implemented to improve the interactive system between Cozmo and the users. Also, a cloud computing vision system was used to perform object recognition using Cozmo’s camera to be applied on educational games. Other functions were created to control Cozmo’s motors and expressions to create sophisticated scripts. To run the scripts, an interpreter algorithm was developed to translate the created functions into Cozmo’s programming language. To validate this work, the project was presented to several elementary school teachers (classes with students between 4 and 12) and the results are reported in this work, indicating that the proposed system can be a useful educational tool. Lastly, in order to reduce the project cost, a simpler system was developed that uses a Raspberry PI to give commands to Cozmo, a computer is no longer necessary.
Development and Integration of a Cloud Based Web Server for Educational Robotics
Keywords: Cozmo; servidor web; robótica educacional; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO